Progress in Regenerative Dentistry Approaches: An Update - Maham shah; Reshma khatoon; Rashid Iqbal; Zaheer Ahmed Soomro; Mohsin Ali Dehraj; Muhammad Amin sahito (Pakistan Journal of Medicine and Dentistry)
Advanced research in biomedical engineering, together with rising treatment standards and the demand for non-conventional methods, have contributed to the explosive growth of the field of dentistry known as regenerative dentistry. Stem cells, scaffolds, and bioactive substances are the three main elements of tissue engineering, the field that forms the basis of regenerative dentistry. Because of these remarkable properties, stem cells produced from dental tissue are very relevant in this field. In a wide spectrum of dental specializations, regenerative techniques have brought novel options to many established treatment protocols. Consider the alternative to conventional root canal therapy provided by pulp revascularization and other regenerative endodontic procedures. Thanks to 3-D bioprinting and computer-aided design, which have revolutionized oral and maxillofacial tissue engineering, modified guided tissue regeneration procedures are gradually replacing standard surgical and nonsurgical periodontal therapy. This paper provides an overview of the most current therapeutic approaches that have been used in clinical settings and highlights the importance of dental tissue-derived stem cells for regenerative dentistry.